The ADM solution of MHD non-Newtonian fluid with transient flow and heat transfer - Shah, Q.; Mamat, M.; Gul, T.; Tofany, N. (2016)
The present study deals with the time dependent motion of magneto-hydrodynamics (MHD) flow of a third grade fluid model with heat transfer. The fluid motion is studied in a porous medium between two inclined and periodically oscillating plates. The governing equations are modeled in the form of nonlinear partial differential equations. The modeled problems are then solved with the help of ADM technique. The physical features of the non-Newtonian fluid model and temperature distribution are presented and discussed the effect of imbedded parameter like local Stock number St, non dimensional variables α, γ1, γ2, γ3, γ4, γ5, γ6 and third grade non-Newtonian parameter β is the non-Newtonian parameter during vibratory motion of fluid flow in a porous medium is the main feature of this work.